2024
DOI: 10.1186/s12875-024-02342-3
|View full text |Cite|
|
Sign up to set email alerts
|

Translation and validation of menopause quick 6 (MQ6) into the Malay language

Anusha Manoharan,
Megat Muhammad Harris,
Beh Hooi Chin
et al.

Abstract: Background Inquiring conservative Asian women about their menopausal symptoms is often challenging in crowded primary healthcare clinics. Furthermore, the subject matter is culturally sensitive to most Malaysian women. Hence, the translation of MQ6 into Malay is crucial to enable self-administration, eliminating the necessity for interviewers and mitigating potential respondent shyness. Methods The Menopause Quick 6 (MQ6) questionnaire was translat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors reported errors in the main body text. Errors were listed in the below table.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported errors in the main body text. Errors were listed in the below table.…”
mentioning
confidence: 99%